Avaliação de estratégias de ventilação natural em salas de aula de ensino fundamental na zona bioclimática 2 - Scherer, Paula (2022)
School classrooms are environments characterized by long permanence, being occupied almost daily by the population. The built conditions of these places, therefore, have great impacts on the energy efficiency of buildings, as well as on the thermal comfort of users. These aspects explain the relevance given to studies on the subject in recent years. Regarding the usage behavior of these places, it appears that the intensity and direction of ventilation in classrooms can impact their energy efficiency and the thermal comfort of users. In addition, due to the need for biosecurity in the face of the COVID-19 pandemic, natural ventilation in school classrooms is of great importance. Furthermore, due to the need for biosecurity, the present research aimed to verify 16 strategies related to natural ventilation of elementary school classrooms in relation to energy efficiency, thermal comfort and the quality of indoor ventilation, for Bioclimatic Zone 2. The methodology was based on simulations with the software EnergyPlus 8.7.0 and with the ANSYS CFX, and thermal comfort criteria recommended by the adaptive model of ASHRAE 55/2017. For the quality of indoor ventilation, OPAS criteria were adopted for ventilation rates and OMS criteria for relative air humidity. The results obtained showed that, for the classroom model studied, natural ventilation strategies caused discomfort rates due to cold above 15%, which were increased when hygienic ventilation was used, reaching 25%. The east-west cross ventilation strategy, with connection, in the west orientation, to a circulation ventilated by lantern, stood out when there was only the use of thermal ventilation, showing satisfactory values of thermal comfort and ventilation quality. It also presented favorable values when there was the application of hygienic ventilation in the upper systems of the north-oriented windows. Strategies with unilateral thermal ventilation, despite showing high thermal comfort, did not introduced the minimum values of ventilation and air renewal rates in the analyzed classroom, which impaired their energy efficiency. This research contributes to a better understanding of opening systems aimed at school buildings that provide quality of indoor ventilation, energy efficiency and thermal comfort for locations in Bioclimatic Zone 2.